Accurate and robust prediction of Amyloid-β brain deposition from plasma biomarkers and clinical information using machine learning - Jiayuan Xu; Andrew J. Doig; Sofia Michopoulou; Sofia Michopoulou; Petroula Proitsi; Petroula Proitsi; Fumie Costen; The Alzheimer's disease neuroimaging initiative (Frontiers in Aging Neuroscience)
BackgroundAlzheimer's disease (AD) greatly affects the daily functioning and life quality of patients and is prevalent in the elderly population. Amyloid-β (Aβ) accumulation in the brain is the main hallmark of AD pathophysiology. Positron Emission Tomography (PET) imaging is the most accurate method to identify Aβ deposits in the brain, but it is expensive and not widely available. The development of a low-cost method to detect Aβ deposition in the brain, as an alternative to PET, would therefore be of great value. This study aims to develop and validate machine learning algorithms for accurately predicting brain Aβ positivity using plasma biomarkers, genetic information, and clinical data as a cost-effective alternative to PET imaging.MethodsWe analyzed 1,043 patients from the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset and validated our models on 127 patients from the Center for Neurodegeneration and Translational Neuroscience (CNTN) dataset. Brain Aβ status was determined using plasma biomarkers [Aβ42, Aβ40, Phosphorylated tau (pTau) 181, Neurofilament light chain (NfL)], Apolipoprotein E (APOE) genotype, and clinical information [Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), age, education year, and gender]. Decision tree, random forest, support vector machine, and multilayer perceptron machine learning methods were used to combine all this information. We introduced a feature selection method to balance the performance and the number of features. We conducted a feature matching technique to enable our model to be tested on the external dataset without retraining.ResultsOur system achieved a value of 0.95 for the Area Under the ROC curve (AUC) using the ADNI dataset (n = 340) and the full set of 11 features. Our architecture was also tested on an external dataset (CNTN, n = 127) and achieved an AUC of 0.90. When using only five features (pTau 181, Aβ42/40, Aβ42, APOE ɛ4 count, and MMSE) on 341 ADNI patients, we achieved an AUC of 0.87.ConclusionThe random forest, support vector machine and multilayer perceptron methods can accurately predict brain Aβ status using plasma biomarkers, genotype, and clinical information. The method generalizes well to an independent dataset and can be reduced to using only five features without losing much accuracy, thus providing an inexpensive alternative to PET imaging.